Sriwedari Mosque Land Dispute, Surakarta Land Law Study - Arvian Putra Ramadhan; Arief Budiono; Robert Lengkong Weku; Jamal Hi Arsad; Faisal Faisal (Universitas Muhammadiyah Surakarta, 2023)
Legal certainty in the land sector is indeed a necessity that must exist, but researchers have found that there are many individuals taking advantage of the weakening of law enforcement which has resulted in an increase in several land disputes. The aim of this research is to identify the factors causing land disputes at the Sriwedari Mosque in Surakarta. This research is research that uses sociological legal methods with a qualitative descriptive approach which was carried out on Jl. Slamet Riyadi Taman Sriwedari, Surakarta city in March-May 2023 using data collection techniques, namely literature study and interviews. Meanwhile, data analysis techniques utilize comparative studies. Based on the research results, the researchers concluded that the chronology of the Sriwedari land, which is now a problem regarding land disputes, was originally purchased by Paku Buwono (PB) This right to land ownership is what caused the land dispute at the Sriwedari Mosque in Surakarta and the construction of the mosque to stop.